The Cosmic Ultraviolet Baryon Survey (CUBS) V: on the thermodynamic properties of the cool circumgalactic medium at z ≲ 1. Issue 4 (9th September 2022) - Qu, Zhijie; Chen, Hsiao-Wen; Rudie, Gwen C; Zahedy, Fakhri S; Johnson, Sean D; Boettcher, Erin; Cantalupo, Sebastiano; Chen, Mandy C; Cooksey, Kathy L; DePalma, David; Faucher-Giguère, Claude-André; Rauch, Michael; et al.
ABSTRACT: This paper presents a systematic study of the photoionization and thermodynamic properties of the cool circumgalactic medium (CGM) as traced by rest-frame ultraviolet absorption lines around 26 galaxies at redshift z ≲ 1. The study utilizes both high-quality far-ultraviolet and optical spectra of background QSOs and deep galaxy redshift surveys to characterize the gas density, temperature, and pressure of individual absorbing components and to resolve their internal non-thermal motions. The derived gas density spans more than three decades, from (n_H/cm^-3) ≈ -4 to −1, while the temperature of the gas is confined in a narrow range of log ( T /K) ≈ 4.3 ± 0.3. In addition, a weak anticorrelation between gas density and temperature is observed, consistent with the expectation of the gas being in photoionization equilibrium. Furthermore, decomposing the observed line widths into thermal and non-thermal contributions reveals that more than 30 per cent of the components at z ≲ 1 exhibit line widths driven by non-thermal motions, in comparison to <20 per cent found at z ≈ 2–3. Attributing the observed non-thermal line widths to intra-clump turbulence, we find that massive quenched galaxies on average exhibit higher non-thermal broadening/turbulent energy in their CGM compared to star-forming galaxies at z ≲ 1. Finally, strong absorption features from multiple ions covering a wide range of ionization energy (e.g. from Mg ii to O iv ) can be present simultaneously in a single absorption system with kinematically aligned component structure, but the inferred pressure in different phases may differ by a factor of ≈10.